Growth Promotion of Rice Plant by Endophytic Fungi - Mamat Kandar; Sony Suhandono; I. Nyoman Pugeg Aryantha (Journal of Pure and Applied Microbiology, 2018)
The main aim of this research is to obtain endophytic fungi from graminiae which has the ability to promote the growth of rice plant. The research was conducted in laboratory of Mycology Research Center for BioSciences and Biotechnology Institut Teknologi Bandung. Isolation of endophytic fungi was done by direct plating of root samples on the potatoe dextrose agar media after surface sterilization steps. Identification was based on morphology characteristics and DNA marker. At least 124 isolates were obtained from elephant grass (Pennisetum purpureum) (27 isolates), alang-alang (Imperata cylindrica) (25 isolates), sugar cane (Saccharum officinarum) (14 isolates), maize (Zea mays) (9 isolates), rice plant (Oryza sativa) (23 isolates) and cyperus (Cyperus rotundus) (26 isolates). Among them, 12 isolates demosntrated the capability to promote the growth of rice seedlings in term of seed germination, plant height, root length and degree of root colonization. Isolate I-11 identified as Phialemonium dimorphosphorum was the best to promote rice plant growth in glass house trial.